Evaluation of a Novel Precordial Lead System for the Electrocardiographic Diagnosis of Right Ventricular Enlargement in Dogs - Giovanni Grosso; Tommaso Vezzosi; Cesara Sofia Pergamo; Martina Bini; Valentina Patata; Oriol Domenech; Rosalba Tognetti (Veterinary Sciences, 2022)
The purpose of this study was to evaluate the reliability of precordial leads for the detection of right ventricular enlargement (RVE) in dogs. This was a prospective observational study. The RVE was defined by echocardiography. The amplitude (mV) of the Q, R, and S waves, the R/S ratio, and the mean electrical axis (MEA) of the QRS complex were assessed on the 12-lead ECG. The ROC curve and the Youden index yielded the best cutoffs for RVE detection. An area under the curve (AUC) > 0.7 defined suitable diagnostic accuracy. A total of 84 dogs, 27 with RVE and 57 healthy controls, were enrolled. Q wave amplitude in aVR (cutoff > 0.10 mV; AUC = 0.727), R/S ratio in V4 (cutoff < 1.15; AUC = 0.842), R/S ratio in V5 (cutoff < 1.95; AUC = 0.839) and S wave amplitude in V6 (cutoff > 0.70 mV; AUC = 0.703) showed suitable diagnostic accuracy in detecting RVE. Among dogs with RVE, only 9/27 (33%) presented a right shift of MEA. Differently, 19/27 (70%) showed at least one of the identified precordial lead criteria. Assessment of the R/S ratio in V4 and V5 and S wave amplitude in V6 increases the diagnostic accuracy of ECG in distinguishing between dogs with RVE and healthy dogs.